The role of bisphosphonate and bone morphogenetic proteins in congenital pseudoarthrosis of the tibia management: a literature review - Panji Sananta; Adithya Stephana Mahendra; Eka Noviya Fuzianingsih (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Congenital pseudoarthrosis of the tibia (CPT) is a rare medical condition characterized by a congenital absence of union in the tibia, which causes the leg to flex anterolaterally. Despite the use of several surgical techniques for the treatment of CPT, there is still a significant risk of failure with surgical interventions. Recent studies have shown that bisphosphonates (BP) and bone morphogenetic proteins (BMP) can be effective adjuncts to surgical procedures, increasing the success rate of bone union and reducing the chance of re-fracture. This review aimed to evaluate the role of BP and BMP in CPT. In this review, a comprehensive literature evaluation was conducted using the PRISMA method. The databases used to search for information included PubMed, ScienceDirect, and Google Scholar for the past 10 years. Six articles were included in this review. The results showed that using pharmacological agents such as BMP and BP is considered safe for pediatric patients as an adjunctive treatment to surgery. This combination can effectively increase the speed of bone union and prevent re-fractures. The small sample size, different protocols, and different doses may have impacted the study results, which should be thoroughly explained.